MAKNA SIMBOLIK SAMBULUGANA PADA UPACARA PERKAWINAN SUKU KAILI (SUATU KAJIAN HERMEUNETIKA) - Andiwa, Andiwa (BAHASANTODEA, 2016)
The problem of this research consist of two sub-problems. Those are, (1) What is the symbols which found at the Sambulu Gana in wedding ceremony of kailinese ethnic, (2) what are the meanings at the symbols Sambulu gana in wedding ceremony of kailinese ethnic. Design and kind of this research can be categorized as a qualitative research with descriptive approach method. There is the data of this research consist of two categorize, those are (1) symbols which found at the sambulu gana in the wedding ceremony of kailinese ethnic. The technique of data accumulation had done through three steps, they are : (1) direct observation, (2) interview, (3), documentation. therefore, all of the data which found explained and investigated with conclude qualitative descriptiveÂ  analisys technique.